DINAMIKA PARTISIPASI MASYARAKAT TERHADAP AKUNTABILITAS KEUANGAN PEMERINTAH KABUPATEN GRESIK PERIODE 2024 - Akilah Nur; Anggun Sri Utami; Farrel Maisya Ramadhan; Theresia Priselis A. L. Koban (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2025)
Community involvement is a critical factor in achieving transparent and accountable village financial management. This study aims to assess the impact of community participation on the accountability of village financial management in Menganti District, Gresik Regency. The research utilized a questionnaire survey method. The findings reveal that most respondents were satisfied with their involvement in village financial decision-making. This involvement positively influences community perceptions of the village government’s performance. The study highlights that community participation enhances public trust in village governance and fosters more transparent and accountable financial management.